Low geriatric nutritional risk index as a poor prognostic biomarker for immune checkpoint inhibitor treatment in solid cancer - Zhang, Lilong; Wang, Kunpeng; Kuang, Tianrui; Deng, Wenhong; Hu, Peng; Wang, Weixing (Frontiers in Nutrition, 2023)
Objective: In this investigation, we focused on the geriatric nutritional risk index (GNRI), a comprehensive metric that takes into account the patient's ideal weight, actual weight, and serum albumin levels to measure malnutrition. Our primary objective was to examine the predictive value of GNRI-defined malnutrition in determining the response to immunotherapy among cancer patients. Methods: Relevant articles for this study were systematically searched in PubMed, the Cochrane Library, EMBASE, and Google Scholar up to July 2023. Our analysis evaluated overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR) as clinical outcomes. Results: This analysis comprised a total of eleven articles encompassing 1417 patients. The pooled results revealed that cancer patients with low GNRI levels exhibited shorter OS (HR: 2.64, 95% CI: 2.08-3.36, p < 0.001) and PFS (HR: 1.87, 95% CI: 1.46-2.41, p < 0.001), and lower ORR (OR: 0.46, 95% CI: 0.33-0.65, p < 0.001) and DCR (OR: 0.42, 95% CI: 0.29-0.61, p < 0.001). Sensitivity analyses confirmed that the above results were stable. Egger's and Begg's tests revealed that there was no publication bias in the above results. Conclusion: Our results imply that the GNRI is a useful predictor of immunotherapy response in cancer patients.